2013
DOI: 10.1002/prca.201200085
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic approach toward personalized sarcoma treatment: Lessons from prognostic biomarker discovery in gastrointestinal stromal tumor

Abstract: Sarcomas range from curable tumors to those causing death via metastasis and recurrence. Thus, there is an urgent need for biomarker identification in order to assess the degree of malignancy, predict prognosis, and evaluate possible therapies. Various proteomic approaches and different clinical materials have been used to this end, and candidate biomarkers have been reported for the different types of sarcomas. However, the sample size used in these biomarker studies was generally insufficient, and thus far, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The proteomic approach is a best indicator of overexpression of oncoproteins like MDM2, regardless of biological mechanisms underlying their overproduction. Unfortunately this approach has been rarely applied to GIST [ 22 ]. We thought that immunohistochemistry, by showing overexpression of a given antigen, reflects partially the proteomic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic approach is a best indicator of overexpression of oncoproteins like MDM2, regardless of biological mechanisms underlying their overproduction. Unfortunately this approach has been rarely applied to GIST [ 22 ]. We thought that immunohistochemistry, by showing overexpression of a given antigen, reflects partially the proteomic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a great therapeutic promise of pharmacologic agents that modulate the MDM2-p53 pathway in GIST and in other types of cancers [ 23 25 ]. Interestingly, a new favorable prognostic biomarker of GIST, named pfetin has been discovered and its immunohistochemical assessment has proven useful in predicting recurrences or metastasis in GIST [ 22 , 26 ]. The next years will probably provide significant insights about the identification of relevant prognostic biomarkers of GIST through robust scientific evidences.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore analyzed two homogeneous human FFPE tissues, gastrointestinal stromal tumor (GIST) [2,44] and liver, by MSI (three full technical replicates each) using five different published methods and propose novel scores for evaluation of homogeneity of on-slide tissue processing and MALDI MSI analysis as well as for quantification of inter-day repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Today, a wide range of proteomics methods, from two-dimensional difference gel electrophoresis (DIGE) in conjunction with matrixassisted laser desorption/ionization (MALDI) mass spectrometry to chemical proteomics based on liquid chromatography in combination with electrospray ionization tandem mass spectrometry (LC-ESI-MS/ MS), are used to study human cancer in tissue extracts [1,2]. In addition, MALDI mass spectrometry imaging (MSI) has recently emerged as a promising technology for analysis of sectioned cancer tissue in preclinical and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group identified pfetin by comparing patient groups who were strictly stratified by prognosis and pathological features. The prognostic utility of pfetin was demonstrated using immunohistochemistry in approximately 500 cases located in six different hospitals [14,15]. Pfetin is one of the most successful tissue biomarkers discovered by proteomics and validated by a conventional method, immunohistochemistry, in an independent sample sets.…”
mentioning
confidence: 99%